2022
DOI: 10.1038/s41467-022-34243-3
|View full text |Cite
|
Sign up to set email alerts
|

Host-dependent resistance of Group A Streptococcus to sulfamethoxazole mediated by a horizontally-acquired reduced folate transporter

Abstract: Described antimicrobial resistance mechanisms enable bacteria to avoid the direct effects of antibiotics and can be monitored by in vitro susceptibility testing and genetic methods. Here we describe a mechanism of sulfamethoxazole resistance that requires a host metabolite for activity. Using a combination of in vitro evolution and metabolic rescue experiments, we identify an energy-coupling factor (ECF) transporter S component gene (thfT) that enables Group A Streptococcus to acquire extracellular reduced fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…GAS resistance to sulfamethoxazole and trimethoprim has been attributed to the mutation of the target enzymes FolP and Dyr, respectively, or the acquisition of trimethoprim-resistant variants of Dyr (DfrF and DrfG) 169,170 . Further, recent work has identified that the energy-coupling factor transporter S component gene (thfT) enables GAS to acquire extracellular reduced folate components directly from the host, bypassing the inhibition of folate biosynthesis by sulfamethoxazole 171 . ThtF requires host metabolites for activity; as such, standard minimum inhibitory concentration (MIC) testing is inadequate for the detection of ThtF-mediated sulfamethoxazole resistance.…”
Section: Sulfamethoxazole Resistancementioning
confidence: 99%
“…GAS resistance to sulfamethoxazole and trimethoprim has been attributed to the mutation of the target enzymes FolP and Dyr, respectively, or the acquisition of trimethoprim-resistant variants of Dyr (DfrF and DrfG) 169,170 . Further, recent work has identified that the energy-coupling factor transporter S component gene (thfT) enables GAS to acquire extracellular reduced folate components directly from the host, bypassing the inhibition of folate biosynthesis by sulfamethoxazole 171 . ThtF requires host metabolites for activity; as such, standard minimum inhibitory concentration (MIC) testing is inadequate for the detection of ThtF-mediated sulfamethoxazole resistance.…”
Section: Sulfamethoxazole Resistancementioning
confidence: 99%
“…The toppling and thermal ratchet mechanism is unprecedented and is a manifestation of the diversity of transport solutions adopted by the ABC transporter superfamily. The fundamental structural and mechanistic insights presented here may have wider implications, since exchange of S-components from different organisms upon horizontal gene transfer may contribute to the ability of bacteria to rapidly acquire new metabolic functionality, or even antibiotic resistance 42 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the interim guidelines from the UK Health Security Agency (UKHSA), co-trimoxazole (SXT; antifolate therapy) is recommended as the second line in case of penicillin allergy ( Table 2 ). However, recent research has shown that when blocked by SXT from producing its own folates, S. pyogenes (isolated from clinical samples) is capable of overcoming susceptibility to SXT by uptaking reduced forms of folic acid directly from the host cells [ 13 ]. This makes the antibiotic ineffective and the patient will likely deteriorate despite antibacterial therapy.…”
Section: Figmentioning
confidence: 99%